Nominal wage rigidities in a new Keynesian model with frictional unemployment - Vincent Bodart; Gregory De Walque; Olivier Pierrard; Henri R. Sneessens; Raf Wouters (Institute for the Study of Labor (IZA), 2006)
In this paper, we propose a search and matching model with nominal stickiness à la Calvo in the wage bargaining. We analyze the properties of the model, first, in the context of a typical real business cycle model driven by stochastic productivity shocks and second, in a fully specified monetary DSGE model with various real and nominal rigidities and multiple shocks. The model generates realistic statistics for the important labor market variables.
urn:nbn:de:101:1-20080429121
Keywords: 330